Comparative Analysis of Institutional Capacity Self-Assessment among Local Governments in Dhankuta - Trital, Nodanath (Journal of Research and Development, 2024)
This study compares local governments' institutional capacity self-assessment (LISA) scores in Dhankuta over four fiscal years.  The objective is to compare and analyze the LISA scores and determine the status of institutional capacity of local governments to service delivery in Dhankkuta. It focuses on comparative analysis of institutional capacity self-assessment. The methodology used in this study is descriptive and analytical approach. The secondary data from self-assessment reports are collected and analyzed with comparing the data of all local governments in Dhankuta over the four fiscal years. This study adopts an analytical descriptive approach and uses document review. The finding reveals that the overall status of local governments has gradually increased in LISA scores over the period. The findings reveal that Pakhribas municipality, Mahalaxmi municipality and Chhatar Jorpati rural municipality have claimed the highest institutional capacity in service delivery area with more than 90 percent self-assessed scores. Similarly, Pakhribas municipality has self-assessed the highest institutional capacity in overall score in FY 2077-78. Shahidbhumi rural municipality has self-assessed the highest process score in FY 2079-80. The Chhatar Jorpati rural municipality has self-assessed the highest quantitative scores among the local governments in FY 2079-80 among all the fiscal years.